Understanding Program Verification - Leino, Rustan (PROLE 2009, San Sebastian, Spain, 2009)
Software quality assurance A major software engineering concern Costly Relies heavily on testing Increasingly helped by advanced tools Verification-condition generation, symbolic execution, model checking, abstract interpretation, fuzzing, test generation